Mechanical properties, structure, bioactivity and cytotoxicity of bioactive Na-Ca-Si-P-O-(N) glasses. (October 2018) - Mabrouk, Assia; Bachar, Ahmed; Atbir, Ali; Follet, Claudine; Mercier, Cyrille; Tricoteaux, Arnaud; Leriche, Anne; Hampshire, Stuart
Abstract: Bioactive glasses are able to bond to bone through formation of carbonated hydroxyapatite in body fluids. However, because of their poor strength their use is restricted to non-load-bearing applications. The effects of nitrogen addition on the physical and mechanical properties and structure of bioactive oxynitride glasses in the system Na–Ca–Si–P–O–N have been studied. Glasses with compositions (mol.%): 29Na2 O–13.5CaO–2.5P2 O5 –(55 −3x)SiO2 –xSi3 N4 (x is the no. of moles of Si3 N4 ) were synthesised with up to 1.5 at% P and 4.1 at% N. A novel 3-step process was used for addition of P and N and this proved successful in minimising weight losses and producing homogeneous glasses with such high SiO2 contents. The substitution of 4.12 at% N for oxygen results in linear increases in density (1.6%), glass transition temperature (6%), hardness (18%) and Young's modulus (74%). Vickers Indentation Fracture (VIF) resistance (K ifr ) was calculated from various relationships depending on the load, indent diagonal, crack lengths and Young's modulus to hardness (E/H) ratio. Firstly, Meyer's index n is calculated from the slope of the logarithmic plot of load versus indent diagonal. Then by comparing the experimental slopes of the logarithmic plots of crack lengths versus load it is concluded that the cracking mode is Radial Median type. The substitution of 4.12 at% N for oxygen results in an increase in K ifr of 40%. These increases in properties are consistent with the incorporation of N into the glass structure in three-fold coordination with silicon which results in extra cross-linking of the glass network. The structure of these bioactive oxynitride glasses was investigated by solid state nuclear magnetic resonance (MAS NMR) of 31 P and 29 Si. The structure reveals that all the N atoms are bonded to Si atoms with the formation of SiO3 N, SiO2 N2 and Q 4 structural units with extra bridging anions at the expense of Q 3 units. The bioactivity of the glasses has been evaluated by soaking them in simulated body fluid (SBF) and results confirm that all these oxynitride glasses are bioactive. Cytotoxicity tests based on different concentrations of these bioactive glass powders in a cell growth environment have also shown that they are not cytotoxic. Graphical abstract: fx1